2020
DOI: 10.1155/2020/4895735
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Karst Caves at Pile Side on the Bearing Capacity of Super-Long Pile Foundation

Abstract: The differences in development and situation of karst caves lead to two kinds of karst caves, and the karst cave may be on the pile side or at the pile bottom, which has a different influence on the bearing capacity of pile foundation. The paper presents a numerical analysis of the influence of karst caves at pile side on the bearing capacity of super-long pile foundation in karst areas. According to the size of pile foundation of a real bridge project, this paper modelized karst caves and investigated the kar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…e determination of foundation bearing capacity is crucial in the design of foundation. erefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [25][26][27][28][29][30][31][32][33][34]. rough the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Test Methodmentioning
confidence: 95%
“…e determination of foundation bearing capacity is crucial in the design of foundation. erefore, the determination of foundation bearing capacity of frozen soil under freezing conditions through tests is also critical for application in practical projects [25][26][27][28][29][30][31][32][33][34]. rough the test and analysis in this chapter, it is concluded that when the temperature gradually decreases, due to the cementation of ice in the soil, the bearing capacity of the foundation will significantly increase.…”
Section: Test Methodmentioning
confidence: 95%
“…Research indicates that currently, many scholars are focusing on the study of settlement issues in bridge pile foundations. And the numerous studies carried out indicate that bad geological conditions (karst area [1][2][3][4][5], groundwater [6][7][8][9]), human engineering activities (foundation pit excavation [10][11][12][13], coal mining [14,15]), and other factors will affect the settlement and deformation of adjacent bridge pile foundation. However, there are few studies on the abnormal uplift of bridge pile foundation, and there is a lack of certain conclusions and theoretical basis.…”
Section: Introductionmentioning
confidence: 99%
“…The bearing capacity of the pile end in a multi-cavity stratum was examined by Liang et al, who concluded that it declined as the cavity diameter increased [13]. By computationally simulating variables such as cavity length, height, and top-plate thickness, Wang et al investigated the impact of cavities on the bearing capacity of super-long pile foundations and concluded that the cavities had little impact on the pile foundations' dynamic response [14]. In numerical simulations of cavern span variations on the bearing characteristics of bridge pile foundations, Feng et al discovered that the pile side friction resistance tends to decrease with increasing cavern span [15].…”
Section: Introductionmentioning
confidence: 99%